Expanding buprenorphine prescribing in primary care: a qualitative study of the experiences of primary care providers and nurse care managers participating in the New York City buprenorphine nurse care manager initiative - Elodie C. Warren; Nisha Beharie; Marissa Kaplan-Dobbs; Asmara Tesfaye Rogoza; Alex Harocopos (Harm Reduction Journal)
Abstract Background Improving access to and retention in evidence-based treatment for opioid use disorder, including buprenorphine, is a critical response to the opioid overdose crisis. To increase the availability of buprenorphine treatment in primary care settings, the New York City Department of Health and Mental Hygiene implemented the Buprenorphine Nurse Care Manager Initiative in safety-net primary care clinics. The initiative funds nurse care managers to coordinate ongoing buprenorphine care and provides clinical support and technical assistance for implementation. Methods As part of a process evaluation of the initiative, we conducted in-depth interviews with 18 primary care providers new to prescribing buprenorphine and five nurse care managers across six organizations in New York City that participated in the Buprenorphine Nurse Care Manager Initiative between 2017 and 2019. We aimed to understand participating providers’ views on the successes and challenges of the initiative. Thematic and trajectory analytic approaches were used to capture major themes and changes over time. Results Findings show that participating providers valued many aspects of the initiative, suggesting that integrating buprenorphine treatment with the support of a nurse care manager into safety-net primary care clinics can effectively expand access to buprenorphine and quality of care for people with opioid use disorder in New York City. Conclusions Findings from this process evaluation can inform future primary care-based buprenorphine treatment initiatives. Recommendations include ensuring ample nurse care manager support for primary care providers, robust mentorship structures, and organizational buy-in for initiative sustainability.